El mito de la salud colectiva - Carlos Mario Uribe-S; Martha Cecilia Arbelaez-R (Universidad de Antioquia, 1997)
The article shows a critical view of the community health care systems from the past to the present. To define the collective health concept, it is basic start to work the significance of three linguistic categories, they will give us a wider knowledge of the previous concepts from: the language, the meanings and the various interpretations, we have to recognize the differences that appear between word and facts and they will show us, the world of meanings. Trough out the mankind history, health has been viewed only from the biologist optics. The social component has had a tangential participation and it has not been deeply identify the relation ship between the former and the health-sickness process. In order to obtain appropied levels of health in differents human groups, it is imperative to solve their basic needs. We have to change the traditional health concept that defines It as the mere absence of disease. It's also necessary to recognize the relationship between health and the macroeconomics politics, to practice the COMM unity participation principles stablished in our political constitution (1991); and to apply all the laws related with the descentralitation of the health processes, in which the people plays an active roll with their basic rights and duties.